A STUDY OF ENGLISH READING COMPREHENSION USING CONTENT-BASED INSTRUCTION APPROACH - Khruawan, Panida; Dennis, Nutprapha K. (International Journal of Research -GRANTHAALAYAH, 2017)
The purposes of this study were to investigate students’ achievement in reading comprehension taught by Content-Based Instruction (CBI) Approach and to study the attitude of students through the approach. The samples of this study were fifty of grade ten students who enrolled English course at Khowangwittayakhom School, Yasothorn. The samples were selected by a simple random sampling. The instrument used in this study consisted of ten content-based instruction lesson plans, reading pre-test and post-test, and questionnaire. The data were analyzed statistically in the form of t-test, arithmetic mean and standard deviation. The research findings as the effectiveness of English reading after using Content-Based Instruction Approach in teaching was significantly higher than before teaching at critical level 0.05 and the students’ attitude toward using Content-Based Instruction Approach was at a good level.